Eggshell derived calcium phosphate and its conversion to dense bodies. - Abd Rahim, Toibah; Mustafa, Zaleha; Misran, Fatimah; Shamsudin, Zurina (Penerbit Akademia Baru, 2020)
Since eggshell waste is one of the many contributors to food waste in Malaysia, recycling activities and proper waste management can help reduce the amount of eggshell waste. The present study discusses the synthesis method of eggshell derived calcium phosphate utilizing recycled eggshell as the calcium precursor and diammonium hydrogen phosphate ((NH4)2HPO4) as the phosphate precursor by a simple hydrothermal reaction when the pH of the solution was adjusted at 9. A rod-like nanostructure of CaP which contains only HA phase was produced following heat treatment at 400 °C using the CaO produced from the recycled eggshell. The effect of sintering temperature ranging between 900 °C and 1250 °C on the dense bodies using the resulting CaP powder was also studied. It was found that the HA phase in the resulting CaP powder was mostly transformed to β-TCP with a trace amount of the HA phase following the sintering process. The increase of sintering temperatures subsequently increased the hardness and density of the sintered bodies. Further, SEM observations showed the formation of denser microstructures by effective pore removal at the higher sintering temperature